Vertical skeletal changes after extraction and non-extraction treatment in matched class I patients identified by a discriminant analysis: cephalometric appraisal and Procrustes superimposition - Philipp Beit; Dimitrios Konstantonis; Alexandros Papagiannis; Theodore Eliades (SpringerOpen, 2017)
Abstract Background In the long-lasting debate of extraction versus non-extraction treatment, the impact of extractions on the skeletal vertical dimension remains rather unclear. The aim of this retrospective research study was to obtain a bias-free sample of morphologically similar borderline patients treated with or without extraction of the four first premolars and to retrospectively evaluate the vertical changes that occurred. Methods A borderline sample of 83 patients, 41 treated with four first premolar extractions and 42 treated without, was obtained by means of discriminant analysis applied to a previously investigated parent sample of 542 class I patients. The pretreatment and posttreatment cephalometric radiographs were analyzed digitally, and seven measurements were assessed for vertical skeletal changes. Also, average tracings between the two treatment groups were evaluated using the Procrustes superimposition method. Results The variables of SN to Go-Gn and Y-axis showed adjusted intergroup differences of − 0.91° and − 1.11° (P = 0.04). Comparing the mean intra-group differences of all the variables simultaneously, a significant difference was found between the two treatment groups (overall P value = 0.04). In the extraction group, only the gonial angle showed a significant decrease (P = 0.01) while the overall P value evaluating the intra-group differences between pre- and posttreatment was significant (overall P value < 0.01). In the non-extraction group, the variable of N-ANS/N-Me showed a significant decrease (P = 0.02) and the overall P value evaluating the intra-group differences between pre- and posttreatment was also significant (overall P value < 0.01). Differences in treatment duration were assessed using a log-normal model and showed that extraction treatment lasted significantly longer than non-extraction treatment (P < 0.01). Conclusions The borderline group of patients identified by the discriminant analysis exhibited similar morphological characteristics at treatment's onset; therefore, the posttreatment changes could safely be attributed to the choice of extraction or non-extraction treatment and not to pre-existing differences. Treatment choice had an impact on the patients' vertical skeletal dimensions. Patients treated with four first premolar extractions showed a slight decrease in the vertical skeletal measurements, whereas non-extraction patient treatment showed a slight increase. The treatment time was also significantly higher in the extraction group.